2022
DOI: 10.1021/acs.jafc.2c00337
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Natural Dihydropteroate Synthase and Development of a Signal-Amplified Pseudo-Immunoassay for the Determination of Sulfonamides in Pork

Abstract: In this study, a type of magnetic photoaffinity-labeled activity-based protein profiling probe for sulfonamide drugs was first synthesized for the purpose of capturing the natural dihydropteroate synthase of Escherichia coli by using simple incubation and magnetic separation. After characterization of its identity with LC-ESI-MS/MS, this enzyme was used as a recognition reagent to develop a direct competitive pseudo-ELISA for the determination of the residues of 40 sulfonamides in pork. Because of the use of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The identity of our recently obtained natural TetR was identified by using the LC-ESI-MS/MS technique, and the procedures were according to our recent report [ 37 ]. After this experiment, its gene sequence and amino acid sequence were obtained from NCBI.…”
Section: Methodsmentioning
confidence: 99%
“…The identity of our recently obtained natural TetR was identified by using the LC-ESI-MS/MS technique, and the procedures were according to our recent report [ 37 ]. After this experiment, its gene sequence and amino acid sequence were obtained from NCBI.…”
Section: Methodsmentioning
confidence: 99%
“…So, DHPS is the receptor of SAs that should recognize all SAs species. By now, there have been several DHPS-based pseudo-ELISA methods ( He et al, 2022 , Liang et al, 2020 , Liang et al, 2019 , Liang et al, 2013 ) and fluorescence polarization assays ( He et al, 2022 , Wang et al, 2015 ) reported for the detection of SAs residues. Among these analytical methods, fluorescence polarization assay is the simplest, rapidest, and most suitable tool for high-throughput analysis of large-scale samples because it does not require the conventional blocking, incubating, and washing steps.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important measures is to detect pesticide residues in agricultural products sensitively and instantly. Presently, the typical detection approaches to pesticide residues include, but are not limited to, high-performance liquid chromatography (HPLC) [3], gas chromatographymass spectrometry (GC-MS) [4], and enzyme inhibition methods [5]. However, these methods generally require complex operation, large volume of samples, and a long time for measurement, so they cannot be applied to on-site food inspection [6].…”
Section: Introductionmentioning
confidence: 99%